Implikasi Politik Identitas Terhadap Sistem Hukum Tata Negara: Studi Perbandingan di Asia Tenggara - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Afifah Tsalatsatun Nisa; Ratih Setiawati; Arelditya Wahyu Putra Haning (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Identity politics in Southeast Asia has had a significant impact on the legal and state planning system. The study analyzes how exploitation of religious, ethnic, and ideological identity in politics affects various aspects, including elections, public policies, and law enforcement. The impact includes social and political polarizations, the weakening of the rule of law, discriminatory policies towards minorities, and conflicts between identity politics and human rights international standards. The response in these regions is diverse, ranging from an inclusive approach that emphasizes pluralism to a repressive approach that limits civil liberties. The study highlights the challenges in balancing group interests with the national interests, as well as the need for legal reform and political education to address political threats on stability, justice and democracy in Southeast Asia. This research also recommends harmonizing regulations, strengthening yudiative institutions, and democratic and human rights education as a solution to overcome these problems.